2000
DOI: 10.1097/00003446-200006000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Otoacoustic Emissions and Tympanometry in Children with Otitis Media

Abstract: MEE results in a significant reduction in TEOAEs even when the effusion is nonmucoid. This suggests that transmission of acoustic energy to and from the middle ear is altered in children experiencing any form of otitis media with effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 15 publications
1
35
0
4
Order By: Relevance
“…Com relação à presença de alteração na orelha média, a timpanometria realizada com tom de sonda de 1000 Hz apresentou uma porcentagem maior de curva timpanométrica tipo B do que a realizada com tom de sonda de 226 Hz, ou seja, detectou um maior número de orelhas com alteração condutivas. A literatura refere uma maior sensibilidade da sonda de 1000 Hz em relação com a de 226 Hz [30][31][32] . Ao relacionar as curvas timpanométricas (Tabela 3) com a relação sinal ruído das EOAT por banda de frequência e resposta total e reprodutibilidade, os resultados observados foram estatisticamente significantes.…”
Section: Resultsunclassified
“…Com relação à presença de alteração na orelha média, a timpanometria realizada com tom de sonda de 1000 Hz apresentou uma porcentagem maior de curva timpanométrica tipo B do que a realizada com tom de sonda de 226 Hz, ou seja, detectou um maior número de orelhas com alteração condutivas. A literatura refere uma maior sensibilidade da sonda de 1000 Hz em relação com a de 226 Hz [30][31][32] . Ao relacionar as curvas timpanométricas (Tabela 3) com a relação sinal ruído das EOAT por banda de frequência e resposta total e reprodutibilidade, os resultados observados foram estatisticamente significantes.…”
Section: Resultsunclassified
“…Koivunen et al [12] have shown that mucoid effusions (glue and mucoid) reduces the emissions more than non-mucoid effusions. Although the quality of middle ear effusion is important, the quantity of effusion predicts the lack of responses in TEOAE measurement [12].…”
Section: Discussionmentioning
confidence: 99%
“…Using pure tones and variations in pressure in the external auditory canal, tympanometry provides an objective measure of tympanic membrane mobility and middle ear pressure. Middle ear fluid, common in infancy, can diminish or obliterate OAE and significantly compromise ABR testing (El-Rafaie, Parker, & Bamford, 1996;Koivun, Uhari, Laitakari, Alho, & Luotonen, 2000). Studies suggest that conductive hearing loss may be the most common cause of infant hearing screening failures, contributing up to 67% of the false positive findings (Boone, Bower, & Martin, 2005).…”
Section: Electrophysiologic Tests Of Auditory Functionmentioning
confidence: 99%